Pengaruh Strategi Bauran Pemasaran (4P) Terhadap Volume Penjualan UMKM Kota Bengkulu di tengah Pandemi COVID-19 (Studi Kasus pada UMKM Kuliner Kota Bengkulu. - Martasari, Yupika; Sularsih Anggarawati (UNIB Press, 2024)
The purpose of this study was to: (1) determine the effect of the product on the sales volume of Culinary MSMEs in Bengkulu City. (2) determine the effect of price on the sales volume of Culinary MSMEs in Bengkulu City. (3) determine the effect of location on Culinary MSME sales volume in Bengkulu City. (4) determine the effect of promotion on Culinary MSME sales volume in Bengkulu City. (5) determine the effect of product, price, location, and promotion on sales volume of Culinary UMKM in Bengkulu City. This research is a quantitative research. The data in this study were obtained from the results of a questionnaire, in analyzing the data using SPSS.26 for Windows. The sample study was 110. The sampling technique used the purposive sampling. The findings show that the product, price, location, and promotion of Culinary MSMEs significant and positive effect on the sales volume of Culinary MSMEs in Bengkulu City in the midst of the Covid-19 pandemic partially. As for the practical advice in this research, Culinary MSME’s practitioners in Bengkulu City can pay attention to each product offered both in terms of taste and quality, it is hoped that they can also innovate products, be able to see competitor distribution, increase promotions to attract consumer attention, and provide security and convenience for consumers, especially during the Covid 19 pandemic. Keyword: Price; Location; covid-19 pandemic; Product; Promotion; Culinary UMKM; Sales Volume.